AsÄlÄ«b TadrÄ«s al-ImlÄ li Gair NÄá¹iqÄ«n bi al-Arabiyyah - Fatkhul Ulum (Jurnal Alsinatuna, 2018)
ImlÄ is in the high position among the branches of language. It constitutes an important foundation for written language. Errors in imlÄ can result in many problems and lead to errors in understanding sentence because of its unclear meaning. Students who are not Arabic speakers encounter many problems when learning this realm. Therefore, it is needed an appropriate method to adapt students language ability with their language level. This study aims to explain several methods of teaching Imla for non Arabic speakers. The suggested method here is adjusted with the four types of imlÄ, namely: ImlÄ ManqÅ«l, Imla ManÅ¼Å«r, Imla MasmÅ«â€™ and Imla IkhtibÄri. Besides it is provided with applicative examples in the teaching of imlÄ based on certain stages that should be taken by a teacher. Thus the teaching can be carried out pleasantly and satisfy all students needs in the lesson.This study uses the method of al-waÅŸfi al-taá¸©lÄ«li, a method that describes the problems that occur, by analyzing the causes and trying to find solutions to these problems.This research shows that the method of al-NuÅŸush al-MutakÄmilah is more effective and suitable for teaching imlÄ for non-Arab students, because it contains many positive things for teaching branches of Arabic.